IMPLIED EXTERNAL COMPETENCES OF THE EUROPEAN UNION - Dragišić, Radmila (Politeia, 2023)
The anthological ERTA case is considered to be a case in which the contours of learning about the implicit external competence of the European Union have been developed. That logically based teaching, which has already been elaborated in detail so far, celebrated its 50th birthday in March 2021. Therefore, it seems justified to remind ourselves of it and explore the extent to which it is relevant today. At the center of our interest is the substantive determination of external implicit competencies, their origin and genesis at the level of the Union, as well as the scope of their application in the post-Lisbon period expressed through selected jurisprudence of the Court of Justice of the European Union. We use analytical and synthetic methods in our research, with content analysis and historical-comparative analysis occupying a central place within them. Ultimately, we conclude that the concise clarification of cases in which the Union has external jurisdiction further strengthens the need to constantly follow the interpretations given by the Court in the ERTA judgment, which can be fertile ground for an overly extensive assessment by that judicial body.
Keywords: European Union; ERTA case; implied external competences; case law; Lisbon treaty